Legal regulation of Specialized Medical facilities for treatment of drug addiction - حمزة المخزومي وليد مرزة; عبيد ريام كريم (Journal of Legal Sciences, 2019)
The increasing use of narcotic drugs and psychotropic substances in the recent period and the accompanying increase in the number of addicts recently on these substances obliged the administration to pay attention to this issue to protect the public health from the dangers of drugs and psychotropic substances. The role of the administration is not limited to dealing with these materials, but rather to provide support, treatment and rehabilitation for drug abusers and psychotropic substances as patients who need these services in accordance with the legislative policy adopted by the state towards the addicts and through the medical facilities concerned with treatment and providing services that help individuals to get rid of One of the problems of adamanoomorphism in the community are righteous individuals. Through research, we highlight the importance of these facilities and their role in providing services and treatment for patients and their effectiveness in reducing the serious effects of the spread of narcotic drugs and psychotropic substances was poor in Iraqi law or laws in the comparative countries of France and Germany.